Chemotherapy in Metastatic NSCLC – New Regimens (Pemetrexed, Nab-Paclitaxel) - Blais, Normand; Hirsh, Vera (Frontiers in Oncology, 2014)
Platinum-based chemotherapy doublets have been the standard approach to first-line therapy for more than a decade. Many randomized trials testing new combinations have not been able to produce significant gains in patient outcomes when these studies have looked at an unselected patient population. The recognition of the biologic importance of histology and molecular features of lung cancer has dramatically impacted on patient care, as can be easily recognized by the advent of targeted therapy for molecularly defined lung cancers. Similarly, for lung cancers without recognized driver mutations, subgroup evaluations of trials based histology has identified that some chemotherapy regimens offer greater benefit in the squamous cell or the non-squamous cell groups. Two such examples are Nab-Paclitaxel and pemetrexed. These have shown improved anti-tumor activity and a decreased toxicity profile compared to standard combinations. Preferential activity in histologic divided patient subgroups can allow the clinician to personalize his approach to care. The role of these two agents in the management of NSCLC will be described in this article.